With a Little Help from my Friends: Mining the Logic behind Israel-Jordan-UAE Water for Electricity Deal - Munin, Nellie (Invest Journal of Sharia & Economic Law, 2024)
In November 2021, Israel, Jordan, and the United Arab Emirates (UAE) began evaluating the feasibility of an agreement under which Israel would supply Jordan with desalinated drinking water and Jordan would provide Israel with electricity generated by solar systems located in Jordan and built by a UAE company. Since both water and electricity can be produced independently””Jordan can desalinate its own water, and Israel can generate electricity from solar power””the article questions the rationale behind this project. It concludes that the agreement’s foundation, both in terms of engineering and legal structure, is heavily rooted in political and psychological theories of trust building. If successful, this initiative could pave the way for broader regional cooperation and normalization.